Quantum rate efficiency of the charge transfer mediated by quantum capacitive states - Sánchez, Yuliana Pérez [UNESP] (2022)
It has been demonstrated that the transfer of electrons between donor and acceptor states is a room-temperature quantum mechanical event wherein quantum capacitive states per se determine the rate of the charge transfer. This analysis establishes quantum capacitance as a key concept governing the rate efficiency with which electrons are transferred between states. This rate efficiency has been particularly demonstrated using redox-active switches assembled over metallic electrodes, where the transfer of charge between the electrode and redox states occurs in a diffusionless regime. This analysis formed the basis for the quantum rate theory of electron transmittance, which predicts (and experimentally confirms) the existence of a limiting value for this charge transfer resistance that complies with the conductance quantum (a conductance constant value of ∼ 77.5 μS or resistance of ∼ 12.9 kΩ). In this study, we evaluated how the quantum rate concept applies to electrochemical reactions in which the transfer of electrons occurs between electrode and redox-free states in solution (electrolyte) mediated by quantum capacitive states within the interface. The quantum capacitive mediation of the electron transfer reaction demonstrates an improvement in electronic communication, with capacitive states effectively acting as a non-adiabatic bridge with a quantum efficiency enabling electrons to hop following a tunnelling mechanism. The quantum efficiency of electron transport surpasses the traditional diffusion-controlled transfer of electrons within a charge transfer resistance limit that complies with ∼ 12.9 kΩ, leading to a maximum electrode-mediated quantum rate efficiency. Applications of the concept allow us to design molecular interfaces with quantum mechanical efficiency for harvesting electrons from the solution phase to solid-state electrodes.